Application value of the contrast-enhanced ultrasound in the diagnosis of orbital retrobulbar tumors - Ping He (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To analyze the characteristics of the contrast-enhanced ultrasound in orbital retrobulbar tumors, and to explore the application value of the contrast-enhanced ultrasound in the diagnosis of orbital retrobulbar tumors.METHODS: The contrast-enhanced ultrasound data of the 52 patients(52 eyes)with orbital retrobulbar tumors in the Fourth People's Hospital of Shenyang from March 2012 to May 2015 were retrospectively analyzed. According to the pathological results, 41 eyes were divided into benign group and 11 eyes were malignant group. The time intensity(TI)curve and quantitative data were obtained by SonoLiver software.RESULTS: The TI curve of benign group mainly showed fast in and slow out mode, while that of malignant group mainly showed fast in and fast out mode. Quantitative data: rise time(RT)and mean transit time(mTT)in malignant group were lower than those in benign group, while there was no significant difference in maximal intensity(IMAX)between the two groups(P>0.05).CONCLUSION: Contrast-enhanced ultrasound can provide imaging basis for the differential diagnosis of orbital retrobulbar tumors which is helpful for the preoperative qualitative diagnosis.